THE APPLICATION OF THE VALUES OF TASAMUH AND TA’AWUN IN THE TEACHING OF AKIDAH AKHLAK TO SHAPE THE CHARACTER - Kfi Rumi Paniti; Kartubi (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the application of the values of tasamuh and ta’awun in Akidah Akhlak instruction to shape the character of eighth-grade students at State Madrasah Tsanawiyah 8 Muaro Jambi. This research is important because student behavior that does not fully reflect attitudes of tolerance, cooperation, and social concern is still observed within the school environment. This study employs a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, with the research subjects being Akidah Akhlak teachers and eighth-grade students. Data analysis was conducted through data reduction, data presentation, and drawing conclusions, while data validity was ensured through triangulation of sources and methods. The results of the study indicate that the application of the values of tasamuh and ta’awun is carried out through classroom instruction, teacher role modeling, school culture, communal worship activities, and social activities that support the formation of students’ Islamic character. The application of these values brings about changes in students’ character, such as an increase in mutual respect for differing opinions, the growth of social awareness and a spirit of mutual aid, improved cooperation among students, and a reduction in individualistic behavior and conflicts within the school environment. Supporting factors for the study include school support and the role of teachers, while inhibiting factors are the influence of the environment outside the school and the low awareness of some students in practicing these values. This study is limited to a single research location and focuses solely on eighth-grade students; therefore, the findings cannot yet be widely generalized. Nevertheless, this study can serve as a reference for the development of character education based on Islamic values in madrasah.This study offers novelty by focusing on the application of two Islamic values tasamuh and ta’awun in formal Akidah Akhlak instruction at the MTs level. It also contributes to strengthening Islamic character education through learning grounded in the values of moderation and social responsibility.